2022
DOI: 10.1017/s0030605321000417
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence indicates the occurrence of the Endangered Kashmir musk deer Moschus cupreus in Uttarakhand, India

Abstract: The Endangered Kashmir musk deer Moschus cupreus occurs in the western Himalayan region from Nepal to Afghanistan, but there is a lack of comprehensive and reliable information on its range. The region also harbours the Endangered Himalayan musk deer Moschus leucogaster, and this range overlap may have led to misidentification of the two musk deer species and errors in the delimitation of their ranges. Here, using genetic analysis of the mitochondrial DNA control region, we examined the phylogenetic relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Occurrence data of musk deer were collected during 2018–2020 in three landscapes of the Western Himalayas, viz., Uttarkashi, Lahaul Valley, and Pangi Valley. We obtained 279 occurrence records of musk deer through primary surveys and from the published studies from the western Himalayan region of India [ 4 , 17 , 18 , 19 , 37 ]. Out of the total, only 220 spatially independent occurrence records of KMD were used for modelling the distribution in the western Himalayan region of India ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Occurrence data of musk deer were collected during 2018–2020 in three landscapes of the Western Himalayas, viz., Uttarkashi, Lahaul Valley, and Pangi Valley. We obtained 279 occurrence records of musk deer through primary surveys and from the published studies from the western Himalayan region of India [ 4 , 17 , 18 , 19 , 37 ]. Out of the total, only 220 spatially independent occurrence records of KMD were used for modelling the distribution in the western Himalayan region of India ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Kashmir musk deer ( Moschus cupreus , henceforth KMD) was only reported from the westernmost limits of the Hindu Kush Himalaya in Jammu and Kashmir, India, and Afghanistan [ 2 , 18 ]. Recent genetic evidence revealed that the musk deer species present in Uttarakhand is a distinct lineage from all other known species [ 4 ], which was subsequently confirmed as KMD in Uttarakhand and central Nepal [ 19 , 20 ]. However, ambiguities still prevail in musk deer about the number of species/sub-species, taxonomy, and distribution in India [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kashmir musk deer has historically been reported and described from the Kashmir region of the Western Himalayas from elevations between 2000 and 4200 asl [4,26,27] although some recent reports of presence of isolated populations from Nuristan, northeast Afghanistan [25], which is the western limit of the species and genetic analysis based on a few tissue samples [28] and species distribution modeling study [29][30][31], have indicated the occurrence of Kashmir musk deer in the Mustang area of central Nepal, which forms the eastern limit of the species. However, the reported occurrence of the species beyond the Kashmir Himalayas may not be true and warrants detailed investigation.…”
Section: Kashmir Musk Deer (M Cupreus Grubb 1982)mentioning
confidence: 99%
“…The Ibex inhabits the higher elevations above the tree line usually preferring rugged and rocky precipitous terrain and dry grassland steppes between 3400 and 4400 m in the Himalayas and 4000-5500 m in the trans-Himalayas [76,106]. It usually grazes on the thickets along the rocky hills and unlike most other caprids, it is known to dig craters through snow to access forage in winters [6,28,76]. The Ibex and Blue sheep are the main prey for the snow leopard, and they share similar habitats at many places such as Nubra Valley and either side of the Zanskar river in Kargil, with Ibex using steeper slopes at higher elevations closer to Blue sheep, which prefer more open pastures at lower elevations [56,106,107].…”
Section: Asiatic Ibex (Capra Siberica Pallas 1776)mentioning
confidence: 99%